The Role of the Intraplaque Vitamin D System in Atherogenesis - Federico Carbone; Fabrizio Montecucco (Scientifica)
Vitamin D has been shown to play critical activities in several physiological pathways not involving the calcium/phosphorus homeostasis. The ubiquitous distribution of the vitamin D receptor that is expressed in a variety of human and mouse tissues has strongly supported research on these “nonclassical” activities of vitamin D. On the other hand, the recent discovery of the expression also for vitamin D-related enzymes (such as 25-hydroxyvitamin D-1α-hydroxylase and the catabolic enzyme 1,25-dihydroxyvitamin D-24-hydroxylase) in several tissues suggested that the vitamin D system is more complex than previously shown and it may act within tissues through autocrine and paracrine pathways. This updated model of vitamin D axis within peripheral tissues has been particularly investigated in atherosclerotic pathophysiology. This review aims at updating the role of the local vitamin D within atherosclerotic plaques, providing an overview of both intracellular mechanisms and cell-to-cell interactions. In addition, clinical findings about the potential causal relationship between vitamin D deficiency and atherogenesis will be analysed and discussed.